Efficacy of aflibercept in patients with neovascular age-related macular degeneration when combined with cataract surgery - A. A. Kuznetsov; E. V. Tur; A. V. Zurochka; V. S. Rykun (Российский офтальмологический журнал, 2018)
Purpose: to study the effectiveness of aflibercept in the treatment of neovascular age-related macular degeneration (AMD) combined with cataract phacoemulsification with intraocular lens (IOL) implantation. Material and methods. A short-term, prospective, controlled, non randomized comparative study of the effect of aflibercept on the changes of visual acuity, the morphometric parameters of the macular area of the retina, and the immunological ophthalmologic status was carried out on 31 patients with neovascular AMD within 1 month after medication usage start. Results. Intravitreal injection of aflibercept leads to a decrease in diffuse retinal edema in the macular area, the size of neuro- and pigment epithelium detachment, and the size of choroidal neovascularization, which in a number of cases was accompanied by an increase in visual acuity, especially with a simultaneous surgical treatment of cataract. Phacoemulsification with IOL implantation neither deteriorates the course of AMD nor affects aflibercept efficacy. The determination of the immune status of tears in the early period after intravitreal administration of aflibercept could not be seen as a relevant method of drug effectiveness assessment. Conclusion. Intravitreal administration of vascular endothelial growth factor inhibitor, aflibercept (Eilea, Bayer Pharma AG, Germany) is an effective method of neovascular AMD treatment including the cases of simultaneous cataract surgery. For citations: Kuznetsov A.A., Tur E.V., Zurochka A.V., Rykun V.S. Efficacy of aflibercept in patients with neovascular age-related macular degeneration when combined with cataract surgery Russian ophthalmological journal. 2017; 10 (4): 20-8. doi: 10.21516/2072-0076-2017-10-4-20-28 (in Russian).